Research on Türkiye's Public Diplomacy Activities in the Context of Strategic Communication Management: The Example of the Presidency Directorate of Communications - Ömer Cenap Özdemir; Raci Taşcıoğlu (Current Perspectives in Social Sciences, 2026)
In the context of strategic communication management, which has become both the main determinant and the most important power of international relations today, public diplomacy is the subject of this study. In this context, the study aims to determine the types of public diplomacy activities carried out by the Presidency’s Directorate of Communications (PDC), which was established to coordinate Türkiye's strategic communication management in the international arena, with a descriptive approach. The study is important and original in terms of examining and addressing the Directorate of Communications, one of the leading institutions in terms of managing, conducting and directing Türkiye's public diplomacy activities, within this framework. The 'Announcements and Activities' made by the Directorate of Communications between July 24, 2018, and August 19, 2022, and published on its official website, were examined with a descriptive approach and subjected to quantitative content analysis. It was found that the institution carried out a total of 295 announcements and activities. These activities were divided into seven different categories, and the most important activities were examined and analysed in terms of public diplomacy within the context of strategic communication. According to the findings, it has been determined that strategic communication components are used intensively in public diplomacy activities and that these activities are mainly carried out in the media field and public administration field, which are among the strategic communication usage areas.